Efektifitas Peran Internal Audit Dalam Mencegah Dan Mendeteksi Kecurangan - Yessy Aryanti Lestari; Yustrida Bernawati (ITB AAS INDONESIA, 2020)
This study aims to explain the role of internal auditor effectiveness in preventing and detecting fraud. The significance costs incurred due to fraud encourages the importance of strategies to overcome. Internal auditors as one of the functions of an independent appraiser help the company to minimize the occurrence of fraud. Therefore, optimizing its role is necessary to consider in preventing and detecting fraud. This role encourages the entity to make the internal audit function more effective. Aspects considered in creating an effective internal audit role are competence, size, independence, activities, management support for internal audit, and gender of CAE.